Comparing The Clear Pronunciation: Which Accents Teacher Should Teach More? - Nur Ain Nun; Putri Adinda Pratiwi; Yani Lubis (Politeknik Kampar, 2023)
Pronunciation is a part of speaking skills which can be directly and clearly observed and known. When someone speaks in English, the person who’s listening will immediately identify the pronunciation of that person as well as the mistakes they made. The main problem is understanding the pronunciation of different accents because students don't fully understand accents and pronunciations from different regions. The aims of this study are: to identify the abilities of English Education students at the State Islamic University of Sumatra Utata in terms of pronunciation from different regions and to identify the difficulties faced by English Education students at the State Islamic University of North Sumatra in learning pronunciation. The research data used descriptive qualitative data. The instruments are notes and a device such as a handphone for the audio. The subject is English Education Study Program students at the Faculty of Teaching and Education, State Islamic University of North Sumatra. While the implementation time is April 21-27 2023. The result is the American accent has the clearest pronunciation with the main reason being taught more since elementary school than the British English accent which is rarely even never taught by the teachers. Teachers should teach the British English accent more due to a lot of students don’t understand the British accent pronunciation to decrease students' difficulties when they face listening tests with a British English accent.